Multidisciplinary Clinical Study on Retinal, Circulatory, and Respiratory Damage in Smoking-Dependent Subjects - Marcella Nebbioso; Annarita Vestri; Magda Gharbiya; Mattia D’Andrea; Matteo Calbucci; Federico Pasqualotto; Serena Esposito; Alessandra D’Amico; Valentina Castellani; Sandra Cinzia Carlesimo; Paolo Giuseppe Limoli; Alessandro Lambiase (Medicina)
Background and Objectives: Cigarette smoking is a widely prevalent risk factor in the global population, despite its well-recognized systemic impact. In this pilot study, an association was hypothesized between alterations in hemorheological and respiratory characteristics and damage at the chorioretinal level, considering that traditional cigarette smoking may increase oxidative stress, platelet activation, and thrombotic phenomena at the systemic level. Fundoscopy can provide information about the characteristics of the cerebral district and the entire circulatory system. Therefore, the aim of this research was to evaluate the impact of cigarette smoking on chorioretinal vascularization and pulmonary and blood parameters through investigations with optical coherence tomography angiography (OCTA), spirometry, and the total thrombus formation analysis system (T-TAS). Materials and Methods: Thirty subjects were recruited, divided into 20 traditional cigarette smokers (SMs) and 10 non-SMs, who underwent a comprehensive ocular examination, including OCTA. Spirometric evaluation and blood sampling were also performed on both groups to study pulmonary functional capacity, as well as T-TAS. Results: An analysis of the obtained data confirmed the systemic impact of smoking, evidenced by an increase in T-TAS and a decrease in forced expiratory volume in 1 s expressed in liters (FEV1 L) in SMs compared to the non-SMs group. Additionally, OCTA revealed a statistically significant alteration in macular vascular density (FD) in the right eye (RE) of the examined SMs. The other parameters evaluated did not show statistically significant differences. Conclusions: It is believed that FD, FEV1, and T-TAS may be promising values in correlating the alterations observed in SMs, as highlighted by the changes detected with OCTA, spirometry, and hemorheological data. Further research is needed to confirm and expand the results already obtained and to evaluate the systemic vascular damage and oxidative stress caused by tobacco consumption.